PENGARUH APLIKASI DISCORD DALAM PEMBELAJARAN DARING TERHADAP HASIL BELAJAR PADA MATAKULIAH KOMPUTER - Ridho, M.Rasyid; Muhaimin, Muhaimin; Harjono, Harry Soedarto (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
This study aims to explain the influence of Discord application in online learning on student learning outcomes and motivation. Quantitative method with quasi-experimental design with 40 samples. Data collection uses tests and questionnaires, analysis data using instrument tests, normality, homogeneity, while hypothetical tests use Wilcoxon, Mann-Whiteney (U), and Spearman tests. The results of post-test experiment class obtained an average score 83.5 higher than control class 61.25. Based on Wilcoxon Test Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha1 received, Mann-Whiteney Test (U) High motivation obtained U= 1,500 Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha2 Low motivation obtained U=0.000 Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha3 received, there is a significant difference between the results of using discord application and using Whatsapp, Spearman Test Asymp.Sig (2-tailed) obtained 0.000 < 0.05, Ha4 received, correlation coefficient value of 0.973** means the relationship between learning motivation variables and learning outcomes is very strong.